The Myth of Cross-Cultural Love in Five Songs by Ebiet G. Ade: A Semiotic Study of Roland Barthes: Mitos Cinta Lintas Budaya dalam Lima Lagu Ebiet G. Ade: Semiotika Roland Barthes - Amirudin (CASA CENDEKIA MEDIA, 2026)
This study aims to interpret the cross-cultural myth of love in five songs by Ebiet G. Ade from the album